2004
DOI: 10.1136/ard.2003.005900
|View full text |Cite
|
Sign up to set email alerts
|

Selective T cell receptor decrease in peripheral blood T lymphocytes of patients with polymyalgia rheumatica and giant cell arteritis

Abstract: Objectives: To investigate the phenotype and T cell receptor (TCR) use in peripheral blood T cells in patients with polymyalgia rheumatica (PMR) and giant cell arteritis (GCA). Methods: Circulating T lymphocyte phenotype and TCR repertoire were studied by flow cytometry using specific monoclonal antibodies in 23 healthy controls and 37 patients with PMR/GCA. Results: Patients with active PMR/GCA showed an inverse relation between naive and memory CD4+ T cells and unchanged expression of activation surface mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…Several reports have demonstrated that CD8 + T cells are decreased, and CD4 + and naive (CD4 + CD45RA + ) T cells are increased in the active phase of PMR on flow cytometry (18)(19)(20). The present patient also showed improvement of clinical symptoms in parallel with an increase in CD8 + CD25 + cells and a decrease in CD4 + CD25 + cells and CD4 + CD45RA + cells.…”
Section: Discussionsupporting
confidence: 72%
“…Several reports have demonstrated that CD8 + T cells are decreased, and CD4 + and naive (CD4 + CD45RA + ) T cells are increased in the active phase of PMR on flow cytometry (18)(19)(20). The present patient also showed improvement of clinical symptoms in parallel with an increase in CD8 + CD25 + cells and a decrease in CD4 + CD25 + cells and CD4 + CD45RA + cells.…”
Section: Discussionsupporting
confidence: 72%
“…The same group demonstrated that the phenotype of circulating T-cells in patients with PMR/GCA is similar to that found in aged healthy subjects, except for the surface markers of naive and memory cells and a striking non-activated phenotype (55). In particular, Lopez-Hoyos and co-workers showed that specific TCR BV changes occur in patients with active disease accompanied by a significant decrease in certain TCRBV families in both CD4+ and CD8+ T-cell subsets, which may favour the participation of a superantigen stimulation in PMR/GCA (54). In both GCA and PMR patients, NKG2D was preferentially expressed on senescent CD4 CD28(-) and CD8 CD28(-), as well as on CD8 CD28 Tcells (55).…”
Section: Review N Innate Immune Responsessupporting
confidence: 63%
“…Molecular analysis of the CD8 + clonotypes showed a restricted TCR repertoire in the patients with a distinct Jbeta gene segment usage (54). Oligoclonality in the CD8 repertoire persisted despite successful control of the disease activity, suggesting that the CD8+ clonotypes are not an epiphenomenon of the inflammation (54). The same group demonstrated that the phenotype of circulating T-cells in patients with PMR/GCA is similar to that found in aged healthy subjects, except for the surface markers of naive and memory cells and a striking non-activated phenotype (55).…”
Section: Review N Innate Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study by Lopez-Hoyos et al found simultaneous depletion in peripheral blood CD4+ and CD8+ subsets of certain TCR Vβ families, in particular Vβ 5.2-3 [45]. The authors speculated that their findings could be due to T cell encounter with a bacterial or viral superantigen, resulting in activation and proliferation of the majority of T cells bearing the particular Vβ element (a few of which could be autoreactive against vessel wall antigens), followed by depletion due to activationinduced cell death.…”
Section: Discussionmentioning
confidence: 98%